Sit and be fit : Parkinson's workout II [videorecording (DVD)] - Wilson, Mary Ann; McCormick, Lori; Fitzner, Bill (Sit and Be Fit, 2006)
Demonstrates exercises that focus on posture, breathing, balance, truck mobility, ankle flexibility and rhythmic stepping.